Electrical and magnetic properties of spherical SmFeO3 synthesized by aspartic acid assisted combustion method. (December 2015) - Yuvaraj, Subramanian; Layek, Samar; Vidyavathy, S. Manisha; Yuvaraj, Selvaraj; Meyrick, Danielle; Selvan, R. Kalai
Graphical abstract: Highlights: SmFeO3 is synthesized by simple combustion method using aspartic acid as the fuel. The particles are spherical in shape with the size ranges between 150 and 300 nm. Cole–Cole plot infers the bulk conduction mechanism. Room temperature VSM analysis reveal the weak ferromagnetic behaviour of SmFeO3 . Mössbauer analysis elucidates the +3 oxidation state of Fe atoms. Abstract: Samarium orthoferrite (SmFeO3 ) is synthesized by a simple combustion method using aspartic acid as fuel. Phase purity and functional groups are analyzed via X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) analysis, which confirms the single phase formation of orthorhombic SmFeO3 . Approximately spherical particles with size range 150–300 nm is revealed by scanning electron microscope (SEM). The conductivity of the material is identified by the single semicircle obtained in the solid state impedance spectra at elevated temperatures. The calculated electrical conductivity increases with increasing temperature, inferring the semiconducting nature of SmFeO3 . A magnetic study at room temperature revealed weak ferromagnetic behaviour in SmFeO3 due to Dzyaloshinsky–Moriya antisymmetric exchange interaction mechanism. Mössbauer analysis confirmed the +3 oxidation state of iron and magnetic ordering of the sample at room temperature.